Development and application of a reverse transcription loop-mediated isothermal amplification combined with lateral flow dipstick for rapid and visual detection of Citrus leaf blotch virus in kiwifruit. (May 2021) - Peng, Qiding; Ning, Jiachen; Xu, Qianyi; Yang, Ting; Wang, Yunru; Zheng, Tianrui; Zhuang, Qiguo; Xi, Dehui
Abstract: Citrus leaf blotch virus (CLBV) commonly occurs in some horticultural crops including kiwifruit. Sichuan Province is one of the major kiwifruit producing areas in southwestern China. In order to investigate the occurrence of CLBV infecting kiwifruit in Sichuan Province, an efficient reverse transcription loop-mediated isothermal amplification (RT-LAMP) combined with a lateral flow dipstick (LFD) was established as an effective diagnostic method for visually detecting the occurrence of CLBV. In the present study, a set of LAMP specific primers were designed based on the conserved region of coat protein gene of CLBV and the RT-LAMP-LFD assay could be accomplished in 60 min after extraction and cDNA synthesis. The optimized RT-LAMP-LFD method showed high specificity and sensitivity to CLBV, and displayed 1000 times higher sensitivity than that of conventional RT-PCR. Furthermore, 90 kiwifruit samples collected from Sichuan Province were screened by this developed method. The results showed that the incidence of CLBV in kiwifruit was 20% in Sichuan Province. Phylogenetic analysis revealed that all the CLBV Sichuan isolates were divided into different branches in group I and has some genetic distance with other host plants like citrus, rose and sweet cherry. Over all, this study provides a time saving and highly efficient diagnostic tool for monitoring CLBV infection status in kiwifruit. Highlights: A rapid and efficient RT-LAMP-LFD method was developed for the detection of CLBV in kiwifruits. The RT-LAMP-LFD could be completed in 60 min (50 min for RT-LAMP, 10 min for LFD) after extraction and cDNA synthesis. The RT-LAMP-LFD method was 1000-fold more sensitive than the conventional RT-PCR. The incidence and genetic variation of CLBV on kiwifruits in Sichuan Province were evaluated.